PENGEMBANGAN E-MODUL BERBANTUAN KVISOFT FLIPBOOK MAKER PADA MATERI USAHA DAN ENERGI UNTUK SISWA SMA KELAS X - Arif, Tia Fitriani; Nasir, Muhammad; Islami, Nur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract : The purpose of this research is to develop e-module teaching materialsassisted by Kvisoft Flipbook Maker on work and energy materials for high schoolstudents in class X. The development of e-modules is carried out as a solution to thedifficulties of learning physics, as well as the lack of use of learning media in thephysics learning process. The type of research used is research and development(R&D) using the ADDIE model which consists of five stages, namely the analysis,design, development, implementation and evaluation stages. The data collectioninstrument was in the form of a validation sheet given to three validators. The dataanalysis technique is by calculating the validation assessment score using the validityindex of the Aiken's V formula. The results showed that the e-module assisted by KvisoftFlipbook Maker on work and energy materials for class X high school students that wasdeveloped met the valid criteria from the validated aspects including aspects of contentfeasibility, learning design aspects, linguistic aspects, aspects of program operationease, aspects of consistency and animation aspect with Aiken's V validity index of 0.87Key Word : E-Module, Kvisoft Flipbook Maker, Work and Energy